Mortality from liver cancer and liver disease in haemophilic men and boys in UK given blood products contaminated with hepatitis C - Darby, S; Ewart, D; Giangrande, P; Spooner, R; Rizza, C; Dusheiko, G; Lee, C; Ludlam, C; Preston, F (1997)
Background. Most people with haemophilia who were treated with blood products before the introduction of virus-inactivation procedures were infected with the hepatitis-C virus (HCV). However, there is little quantitative information about the long-term effects on mortality of such infection. Methods. We carried out a cohort study of mortality from liver cancer and liver disease in 4865 haemophilic men and boys in the UK. They were treated between 1969 and 1985 with blood products carrying a high risk of HCV infection, and were followed up from first recorded exposure to Jan 1, 1993. Findings. Based on death-certificate information, mortality was 167 times higher than in the general population for liver disease (95% CI 12.5-22.0; 51 deaths), and 5.6 times higher (1.8-13.0; five deaths) for liver cancer. For men and boys with severe haemophilia who were not infected with HIV-1, the cumulative risks of death from chronic or unspecified liver disease or from liver cancer in the 25 years since first recorded exposure to high HCV-risk products were 1.4% (0.7-3.0) at all ages, and 0.10% (0.01-0.7), 2.2% (0.8 and 6.1), and 14.3% (4.5-40.9) for those with first recorded exposure at ages under 25, 25-44, and 45 or older. For those with haemophilia and HIV-1 infection, the corresponding risks were 6.5% (4.5-9.5) at all ages, and 3.8% (2.1-6.8), 17.1% (10.0-28.5), and 18.7% (6.4-47.6) in the three age-groups. In those with severe haemophilia, age-standardised all-cause mortality was stable during 1969-84 but increased during 1985-92 in both HIV-1-infected and HIV-1-uninfected groups. Among those not infected with HIV-1, the increase in all-cause mortality resulted largely from deaths attributed to chronic or unspecified liver disease or liver cancer in men aged over 45. Interpretation. There is an emerging risk of mortality from liver disease and liver cancer in the UK haemophilia population in individuals both infected and uninfected with HIV-1, which probably results from infection with hepatitis C.